Different manifestations of enhanced π-acceptor ligation at every redox level of [Os(9-OP)L2]n, n = 2+, +, 0, − (9-OP− = 9-oxidophenalenone and L = bpy or pap). Issue 45 (1st November 2016) - Hazari, Arijit Singha; Paretzki, Alexa; Fiedler, Jan; Zalis, Stanislav; Kaim, Wolfgang; Lahiri, Goutam Kumar
Abstract : Enhanced metal–ligand and ligand–ligand interactions are promoted in an osmium complex with non-innocent donor and acceptor ligands. Abstract : The title complexes were isolated as structurally characterised compounds [Os II (9-OP)L2 ]ClO4, L = 2, 2′-bipyridine (bpy) or 2-phenylazopyridine (pap), and were compared with ruthenium analogues. A reversible one-electron oxidation and up to three reduction processes were observed by voltammetry (CV, DPV) and spectroelectrochemistry (UV-vis-NIR, partially EPR). Supporting calculations (DFT, TD-DFT) were used to assess the oxidation state combinations of the different redox active ligands and of the metal, revealing the effects of Os versus Ru exchange and of bpy versus pap acceptor ligation. Several unexpected consequences of these variations were observed for members of the new osmium-containing redox series. Remarkably, the EPR results exhibit a clear dichotomy between the complex ion [Os III (9-OP − )(bpy)2 ] 2+ and the radical species [Os II (9-OP˙)(pap)2 ] 2+, which has not been similarly observed for the analogous [Ru III (9-OP − )L2 ] 2+ systems. This difference, unprecedented for 5d n systems, is attributed to the superior stabilisation of the Os II state by the strongly π-accepting pap ligands. The reduced forms [Os II (9-OP − )(pap˙ − )(pap)] and [Os II (9-OP − )(pap˙ − )2 ] − exhibit strong inter-ligand interactions, leading to spin isomers and electron hopping.